Polydopamine/IR820 nanoparticles as topical phototheranostics for inhibiting psoriasiform lesions through dual photothermal and photodynamic treatments. (8th September 2022) - Nirmal, G. R.; Lin, Zih-Chan; Lin, Chih-Hung; Sung, Calvin T.; Liao, Chia-Chih; Fang, Jia-You
Abstract : Dual photothermal and photodynamic therapy (PTT and PDT) is an attractive approach that generates a synergistic effect for inhibiting keratinocyte hyperproliferation in the treatment of psoriasis. Abstract : Dual photothermal and photodynamic therapy (PTT and PDT) is an attractive approach that generates a synergistic effect for inhibiting keratinocyte hyperproliferation in the treatment of psoriasis. Here, we developed phototheranostic nanocarriers capable of producing hyperthermia and reactive oxygen species (ROS) in response to near-infrared (NIR) illumination. To this end, IR820 with photothermal and photodynamic features was embedded in nano-sized polydopamine (PDA) acting as a PTT agent. A comprehensive characterization of the PDA/IR820 nanosystem was performed according to its morphology, size, zeta potential, UV absorbance, and heat generation. Its therapeutic efficacy was assessed by a keratinocyte-based study and using an imiquimod (IMQ)-stimulated psoriasiform murine model. PDA/IR820 nanoparticles were facilely internalized into keratinocytes and mainly resided in lysosomes. Upon irradiation with NIR light, ROS were generated inside the keratinocytes to cause a photodynamic effect. The live/dead cell assay and cytotoxicity assay demonstrated that PDA and IR820 acted as effective photoabsorbers to induce keratinocyte death. The highest cytotoxic effect was detected in the group of NIR-irradiated PDA/IR820 nanoparticles, which killed 52% of keratinocytes. The nanosystem acted through the caspase and poly ADP-ribose polymerase (PARP) pathways to induce keratinocyte apoptosis. In vitro and in vivo skin permeation indicated the selective accumulation of the topically applied PDA/IR820 nanoparticles within psoriasiform skin, suggesting their skin-targeting capability. The combination of PDA/IR820 nanoparticles and NIR irradiation increased the skin temperature by 11.7 °C. PTT/PDT eliminated psoriasiform plaques in mice by decreasing hyperplasia, inhibiting cytokine overexpression, and recovering the barrier function. The epidermal thickness of the IMQ-treated skin was reduced from 134 to 34 μm by the nanocarriers plus NIR. The IR820 nanoparticles were largely deposited on the inflamed areas of psoriasiform lesions for monitoring the severity of inflammation. The image-guided phototheranostic nanoparticles showed their potential for applications in psoriasis management via noninvasive topical administration.